The Indigenous Digital Divide: COVID-19 and its impacts on education delivery to First Nations university students - Wilson, Arthur; Downing, Mandy; Buckley, Amma; Owen, Julie; Jackson, Max (2022)
The global COVID 19 pandemic highlighted that the delivery of online education inadvertently disadvantaged Indigenous Australian university students. This situation was particularly critical for Indigenous students from rural and remote locations. Australian universities increased the use of digital technologies to engage, support and teach due to students’ inability to access campuses. This presented universities with challenges in supporting Indigenous students living in and returning to non-urban settings. Often not recognised is the need for better strategies and plans for Indigenous students returning to their rural or remote community to continue their studies due to COVID. These communities often lack suitable infrastructure that would allow access to pedagogical and learning support opportunities. This paper explores how the business decision made by Australian universities to increase reliance on teaching online during COVID impacted the education of Indigenous students. This paper will then canvas ways this ongoing dilemma can be addressed by considering risks, measuring and monitoring performance to guide transformation, including universities’ more inclusive and respectful use of digital technologies involving First Nations people and cultures.